VALUATION OF PT PEGADAIAN FOR PROPOSED IPO PRICE - Ratna Pertiwi, Annisa
PT Pegadaian aspires to be the most valuable financial company in Indonesia and as the public's first choice financial inclusion agent. To achieve that, PT Pegadaian planned becomes a public company. PT Pegadaian can distribute more financing with increasing capital facilities. PT Pegadaian has planned to do an initial public offering (IPO). This study aimed to analyze and estimate the intrinsic value of Pegadaian This study will be analyzing PT Pegadaian using external analysis, internal analysis, financial ratio analysis, and SWOT analysis. Toward estimating the intrinsic value used absolute and relative valuation model. The absolute valuation model used is the free cash flow to equity (FCFE) model and the excess return model. The relative valuation used that are price to earnings ratio and price to book value ratio. The intrinsic value using the free cash flow of the equity model estimated is IDR 2.383,73 /share. Using the scenario analysis with Monte Carlo simulation, the result is obtained the range of intrinsic value that is IDR 632,36 – 2.080,06/share. The intrinsic value using the excess return model estimated is IDR 2.571,41/share. Using the scenario analysis using Monte Carlo simulation, the result is obtained the range of intrinsic value that is IDR 658,22 – 2.240,00/share. The valuation using the price to earnings ratio has resulted is IDR 981,35/share. Then, the result of intrinsic value using the price to book value ratio is IDR 1.206,39/share. Based on analyzed using the external analysis, internal analysis, financial ratio analysis, and SWOT analysis, then further the weighted average result of the absolute and relative valuation model, the intrinsic value of Pegadaian when IPO estimated around IDR 2.357,97/share. The researcher suggests recommendations to investors to buy PT Pegadaian stock during the IPO.